2019
DOI: 10.1002/clen.201900203
|View full text |Cite
|
Sign up to set email alerts
|

Responses in Phenotypic Plasticity of Amaranthus palmeri and Polygonum orientale to Soil Factors under Different Habitats

Abstract: The extension and structure of functional traits variation in response to different soil factors between invasive and native plants are poorly understood. Functional traits and soil factors of the invasive plant Amaranthus palmeri and its coexisting plant Polygonum orientale are investigated under three heterogeneous habitats: roadside (rs), wasteland (wl), and riverbank (rb) in Tianjin, China. The shoot dry weight (SDW) and leaf nitrogen (LN) of A. palmeri are significantly higher compared with P. orientale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…There is a correlation between the viability of Amaranthus palmeri seeds and vigor during artificial aging. After 3 years of naturally existing in soils in Nebraska, vigor of Amaranthus palmeri seeds was found to be less than 10% [19,57]; after 5 months of waterflooding, their vigor was found to be 86% [18]. Therefore, Amaranthus palmeri seeds exhibit a certain tolerance to short-term high temperatures and high humid environments [58,59].…”
Section: Effects Of Different Salt Concentrations Onmentioning
confidence: 99%
“…There is a correlation between the viability of Amaranthus palmeri seeds and vigor during artificial aging. After 3 years of naturally existing in soils in Nebraska, vigor of Amaranthus palmeri seeds was found to be less than 10% [19,57]; after 5 months of waterflooding, their vigor was found to be 86% [18]. Therefore, Amaranthus palmeri seeds exhibit a certain tolerance to short-term high temperatures and high humid environments [58,59].…”
Section: Effects Of Different Salt Concentrations Onmentioning
confidence: 99%
“…Greater plasticity is hypothesized to correlate with high heterogeneity in resource availability [ 3 - 6 ]. Many studies have been focused on plant plasticity in relation to spatial-scale environmental heterogeneity [ 7 - 9 ], much less attention has been paid to the relationship between time-scale environmental heterogeneity and plasticity. However, temporally heterogeneous environments may be more ubiquitous than environmental heterogeneity at spatial scale, plants can experience fluctuations in light, water and nutrient availability at scales of hours, days and months in their lifetime It is reported that Convolvulus chilensis experiencing the greatest temporal variation in nature has shown the greatest plasticity in four traits [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of A. palmeri will result in significant yield losses if not fully controlled, and it has been regarded as the most agronomically challenging species in the United States [26,27]. In recent years, A. palmeri has spread rapidly throughout the Beijing-Tianjin-Hebei region of northern China, displacing native plants and endangering local biodiversity [28]. Previous studies have already indicated that A. palmeri invasion enhanced functional traits (i.e., leaf number, plant height, and total biomass) [29], altered soil chemical and biological properties (e.g., total carbon, ammonium nitrogen, and soil extracellular enzyme activities) [30], and influenced bacterial composition and co-occurrence patterns [31].…”
Section: Introductionmentioning
confidence: 99%